Penerapan Pencatatan Keuangan Sederhana Terhadap Efektivitas Pengelolaan Keuangan UMKM Kedai Risol Mayoku Pasuruan - Deswita Ayu Maharani; Muhafidhah Novie; Chairil Anwar (JURNAL AKUNTANSI BARELANG, 2026)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are essential to the country's economy, but a lack of organized record-keeping makes it difficult for many business owners to manage their finances. This study uses a qualitative approach and a case study design to investigate how basic financial record-keeping affects the efficacy of financial management at the Kedai Risol Mayoku MSME. Semi-structured interviews, direct observation, and financial record documentation were used to collect data, which was then subjected to thematic analysis. The findings show that keeping a daily cash book aids business owners in tracking cash flow, comprehending revenue and expenses, and routinely assessing their company's performance. It also supports operational decision-making, including capital management and raw material procurement planning. However, there are still challenges with recording consistency, particularly during periods of high economic activity. In general, basic financial record-keeping enhances MSME financial management's efficacy. Therefore, to maximize financial management, greater record-keeping discipline and the application of more useful technologies are required.